Recent progress of thermocatalytic ammonia synthesis via an associative mechanism - Yangyu Zhang; Jiaxin Li; Yanliang Zhou; Chak-tong Au; Xiuyun Wang; Lilong Jiang (Fundamental Research, 2025)
Ammonia is an important chemical and a carrier of hydrogen. Artificial nitrogen fixation mainly relies on the Haber−Bosch process driven by thermo-catalysis, where the activation of N2 usually follows a dissociative route. Nonetheless, an associative route is common in electrocatalytic or biological nitrogen fixation under ambient conditions. Recently, it was reported that N2 can be activated via an associative mechanism in thermocatalytic ammonia synthesis over some special catalytic materials or active sites, which exhibits enormous potential to realize efficient ammonia synthesis under relatively mild conditions (≤ 400 °C and ≤ 1 MPa). In this review, we focus on the recent progress of ammonia synthesis that follows an associative mechanism. Besides the hydride and nitride materials, the catalysts with highly dispersed active sites are included. We discuss the key factors that drive N2 activation via an associative route and examine their correlation with catalytic performance. Finally, we delve into the perspectives of catalyst design tailored to facilitate an associative mechanism.